Cabozantinib versus sunitinib as initial therapy for metastatic renal cell carcinoma of intermediate or poor risk (Alliance A031203 CABOSUN randomised trial): Progression-free survival by independent review and overall survival update. (May 2018) - Choueiri, Toni K.; Hessel, Colin; Halabi, Susan; Sanford, Ben; Michaelson, M. Dror; Hahn, Olwen; Walsh, Meghara; Olencki, Thomas; Picus, Joel; Small, Eric J.; Dakhil, Shaker; Feldman, Darren R.; et al.
Abstract: Background: The randomised phase 2 CABOSUN trial comparing cabozantinib with sunitinib as initial therapy for advanced renal cell carcinoma (RCC) of intermediate or poor risk met the primary end-point of improving progression-free survival (PFS) as assessed by investigator. We report PFS by independent radiology review committee (IRC) assessment, ORR per IRC and updated overall survival (OS). Patients and methods: Previously untreated patients with advanced RCC of intermediate or poor risk by IMDC criteria were randomised 1:1 to cabozantinib 60 mg daily or sunitinib 50 mg daily (4 weeks on/2 weeks off). Stratification was by risk group and presence of bone metastases. Results: A total of 157 patients were randomised 1:1 to cabozantinib (n = 79) or sunitinib (n = 78). Median PFS per IRC was 8.6 months (95% confidence interval [CI] 6.8–14.0) versus 5.3 months (95% CI 3.0–8.2) for cabozantinib versus sunitinib (hazard ratio [HR] 0.48 [95% CI 0.31–0.74]; two-sided p = 0.0008), and ORR per IRC was 20% (95% CI 12.0–30.8) versus 9% (95% CI 3.7–17.6), respectively. Subgroup analyses of PFS by stratification factors and MET tumour expression were consistent with results for the overall population. With a median follow-up of 34.5 months, median OS was 26.6 months (95% CI 14.6–not estimable) with cabozantinib and 21.2 months (95% CI 16.3–27.4) with sunitinib (HR 0.80 [95% CI 0.53–1.21]. The incidence of grade 3 or 4 adverse events was 68% for cabozantinib and 65% for sunitinib. Conclusions: In this phase 2 trial, cabozantinib treatment significantly prolonged PFS per IRC compared with sunitinib as initial systemic therapy for advanced RCC of poor or intermediate risk. Trial Registration Number: NCT01835158 . Highlights: Cabozantinib was evaluated vs sunitinib as initial therapy for advanced renal cell carcinoma(aRCC) of intermediate/poor risk. Improved progression-free survival (PFS) per investigator with cabozantinib was previously reported. PFS per independent assessment was significantly prolonged with cabozantinib. PFS for subgroups were consistent with results for the overall population. Cabozantinib may be an initial treatment option for patients with aRCC of intermediate or poor risk.